EMBR-10. INOSITOL TREATMENT INHIBITS MEDULLOBLASTOMA THROUGH SUPPRESSION OF EPIGENETIC-DRIVEN METABOLIC ADAPTATION. (1st June 2021) - Badodi, Sara; Pomella, Nicola; Zhang, Xinyu; Morrison, Gillian; Pollard, Steve M; Bennett, Christopher D; Clifford, Steven C; Peet, Andrew; Marino, Silvia
Abstract: Medulloblastoma (MB) is the most common paediatric malignant brain tumour and is classified into four distinct molecular subgroups (WNT, SHH, G3 and G4), each of them further subdivided into subtypes with different prognosis and responses to therapy. Deregulation of chromatin modifier genes plays an essential role in MB, particularly in the G4 subgroup, the least understood of all subgroups, despite being the most common and associated with poor prognosis. A BMI1 High ; CHD7 Low molecular signature identifies patients with poor survival within this subgroup. We show that BMI1 High ; CHD7 Low mediates a novel epigenetic regulation of inositol metabolism in both G4 MB cells and patients. These tumours display hyperactivation of the AKT/mTOR pathway which leads to energetic rewiring characterized by enhanced glycolytic capacity and reduced mitochondrial function. We demonstrate that inositol administration counteracts this metabolic alteration, impairs MB proliferation in vitro and significantly extends survival in an in vivo pre-clinical model. Moreover, inositol synergises with cisplatin, a chemotherapy agent currently used in MB treatment, enhancing its therapeutic effect in vivo . Importantly, cerebellar neural stem cells bearing the BMI1 High ; CHD7 Low signature do not show metabolic adaptation and are thus resistant to inositol treatment, highlighting a fundamental difference between normal and neoplastic metabolism in the developing cerebellum. In summary, we have identified an actionable vulnerability in a pre-clinical setting modelling a molecularly defined group of MB patients, the translational value of which can now be explored in signature-matched clinical trials in MB.